Analysis Of Factors Affecting Consumer Satisfaction and Loyalty Toward Bulog Rice In Mojokerto Regency - Armana, Andru; Soedarto, Teguh; Atasa, Dita (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2026)
This study aims to analyze the influence of product quality, price, agent service, sales location, and brand image on consumer satisfaction and loyalty toward BULOG rice in Mojokerto. Using a quantitative approach with 100 respondents selected through purposive sampling, data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) in SmartPLS. The results indicate that while product quality, agent service, and sales location significantly influence satisfaction, they function as "hygiene factors" with small effect sizes. A notable "price disconnect" was identified: affordability strongly drives satisfaction (p=0.007) but fails to significantly foster loyalty (p=0.265). Conversely, brand image does not influence satisfaction (p=0.845) but acts as a "security anchor" that directly sustains loyalty (p=0.014) through institutional trust. Predictive relevance was confirmed using the PLSpredict procedure, showing robust Q2 values of 0.497 for satisfaction and 0.620 for loyalty. These findings suggest that BULOG should pivot from general marketing to operational excellence, focusing on quality SOPs and standardized agent services to transform institutional credibility into lasting consumer commitment.